2022
DOI: 10.1093/tas/txac060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of feeding dried distillers grains with solubles on Boer goat growth performance, meat color stability, and antioxidant capacity

Abstract: A total of 72 male Boer goat kids (21.7 ±0.5 kg) were fed for 21-d with 3 kids per pen and 12 pens per treatment. Dietary treatments were: 0% inclusion of dried distillers grains with solubles (DDGS; 0% DDGS); or 33% DDGS inclusion (33% DDGS) and were provided ad libitum. Goats and feeders were weighed weekly to collect body weights (BW) and determine feed disappearance in order to calculate average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (G:F). At the conclusion of the feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
2
1
3
Order By: Relevance
“…Findings of this research regarding carcass traits were in agreement with findings by Dahmer et al (2022) [ 38 ], where they found no difference in dressing percentage, LMA, and fat thickness when Boer goats were fed with either 0% DDGS or 33% DDGS diets for 21 days. Gurung et al (2009) [ 13 ] also reported similar findings in Kiko x Spanish male goats of 4–5 months of age fed with 0%, 10%, 20%, and 30% DDGS diets.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Findings of this research regarding carcass traits were in agreement with findings by Dahmer et al (2022) [ 38 ], where they found no difference in dressing percentage, LMA, and fat thickness when Boer goats were fed with either 0% DDGS or 33% DDGS diets for 21 days. Gurung et al (2009) [ 13 ] also reported similar findings in Kiko x Spanish male goats of 4–5 months of age fed with 0%, 10%, 20%, and 30% DDGS diets.…”
Section: Discussionsupporting
confidence: 92%
“…In a trial by Dahmer et al (2022) [ 38 ], back fat thickness was only 1.1 mm for Boer goats fed 0% DDGS and 1.0 mm for goats fed 33% DDGS, which is less than the back fat thickness observed in this experiment. This might be because fat content in the diet provided to goats by Dahmer et al (2022) [ 38 ] was 2–3%, whereas fat content in this experiment was 4–5%.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations